Katie the catsitter. Secrets and sidekicks - Venable, Colleen A. F.; Yue, Stephanie (New York : Random House, 2023)
Still training to be a sidekick, Katie protects the city against mysterious robot attacks--while trying not to feel like an outsider within her own friend group.
3.8
3-6
Keywords: Supervillains -- Comic books, strips, etc; Supervillains -- Juvenile fiction; Pet sitting -- Comic books, strips, etc; Pet sitting -- Juvenile fiction; Friendship -- Comic books, strips, etc; Friendship -- Juvenile fiction; Supervillains -- Fiction; Pet sitting -- Fiction; Friendship -- Fiction; Graphic novels; Comics (Graphic works)